Penerapan Strategı Pemasaran Dıgıtal Pada Toko Unıted Statıonery - Jimmy Pratama; Alex Sandro (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The purpose of this community service activity (PKM) is to help solve the problems that exist in SMEs in Batam City. The partner in this activity is the United Stationery Store which is currently focusing on the online wholesale sector. So in this activity the author will help the United Stationery Store design a digital marketing system that suits the needs of the United Stationery Store, namely facebook shop, facebook ads, instagram ads, google ads, e-brochures, and e-catalogs. This activity was carried out using the interview method and community education. The result of the implementation of this activity is that the United Stationery Store has been able to implement the designed digital marketing system. Of all the systems implemented, google ads is a very effective marketing system at this time, then facebook shop and instagram ads. Facebook ads are the most ineffective or ineffective system compared to other systems. The author recommends that the United Stationery Store in the future can implement digital marketing compared to conventional marketing and the United Stationery Store can consider digital marketing with google ads, facebook shop, and instagram ads, especially google ads.